2007
DOI: 10.1063/1.2458162
|View full text |Cite
|
Sign up to set email alerts
|

Probing bactericidal mechanisms induced by cold atmospheric plasmas with Escherichia coli mutants

Abstract: Mechanisms of plasma-induced microbial inactivation have commonly been studied with physicochemical techniques. In this letter, Escherichia coli K-12 and its ΔrecA, ΔrpoS, and ΔsoxS mutants are employed to discriminate effects of UV photons, OH radicals, and reactive oxygen species produced in atmospheric discharges. This microbiological approach exploits the fact that these E. coli mutants are defective in their resistance against various external stresses. By interplaying bacterial inactivation kinetics with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(105 citation statements)
references
References 24 publications
1
104
0
Order By: Relevance
“…1). The minor roles of UV photons and positive or negative particles may also play a part (Perni et al, 2007). ROS---for instance superoxide radicals or hydroxyl radicals---seems to be the main contributor to the plasma antibacterial activity (Boudam et al, 2006;Gaunt et al, 2006 (Berlett and Stadtman, 1997).…”
Section: Role Of Plasma Species and Functional Moleculesmentioning
confidence: 99%
“…1). The minor roles of UV photons and positive or negative particles may also play a part (Perni et al, 2007). ROS---for instance superoxide radicals or hydroxyl radicals---seems to be the main contributor to the plasma antibacterial activity (Boudam et al, 2006;Gaunt et al, 2006 (Berlett and Stadtman, 1997).…”
Section: Role Of Plasma Species and Functional Moleculesmentioning
confidence: 99%
“…This can filter out the effects of some ROS/RNS, since their concentrations at the cell/tissue location may fall below the threshold of their biological effects. For example, current evidence of bacterial inactivation studies suggests that UV photons play a less important role than ROS [92]- [94]. Figure 2 shows a damaged membrane of B. subtilis spores after plasma treatment, typical of a result of oxidation.…”
Section: Reactive Plasma Species and Their Biological Targetsmentioning
confidence: 99%
“…Studies using isolated protein and plasmid DNA models have shown protein and DNA damages [95]- [99], and more relevant experiments using bacterial cells have provided direct evidence of breaching and rapture of cell membrane [100], reduction and degradation of proteins [101]- [103], lipid damage [104], and (mostly) single-strand breaks (SSB) of DNA [105]. These results have prompted the suggestion of the involvement of ROS, charged particles, and UV photons [92][100] [105] - [108], with ROS often linked to oxidation of protein and lipid and with UV photons linked to DNA damages. The view of DNA damages, particularly double-strand breaks (DSB), being largely induced by UV and shorter-wavelength radiation has its root in radiation biology where many hundreds of DSBs per microorganism are not uncommon among irradiated bacteria [109].…”
Section: Reactive Plasma Species and Their Biological Targetsmentioning
confidence: 99%
“…The high-energy electrons, ions, other active particles and the ultraviolet rays during the discharge have, to some extent, an inactivation effect on the microorganisms [28]. This kind of inactivation effect is achieved by their damage on the cytomembrane, cytoderm and the genetic material.…”
Section: Sterilization Effectmentioning
confidence: 99%